Pengembangan Aplikasi Digital Village sebagai Bentuk Optimalisasi Birokrasi Desa Pandan Kecamatan Slogohimo Kabupaten Wonogiri - Rinata Permana Jati; Arif Sutikno; Moenawar Kholil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop the Digital Village application (SMAPAN) as a form of bureaucratic optimization in Pandan Village, Slogohimo District, Wonogiri Regency. The problems identified include manual administrative services, unintegrated data management, and limited public access to village information. This research uses the Research and Development (R&D) method with the ADDIE development model, covering the stages of analysis, design, development, implementation, and evaluation. The application was developed using Visual Studio Code, the Laravel framework, and Laragon as the local development environment. Data were collected through observation, interviews, documentation, and questionnaires, then analyzed descriptively using a Likert scale percentage. The product was validated by one media expert, one material expert, and three village-apparatus practitioners, followed by a limited trial involving three respondents. The results show that the application was successfully developed with features including a homepage, village profile, letter-request services, user registration and login, an administrator dashboard, letter management, village announcements, and PDF letter printing. The media expert validation obtained a percentage of 88.42% (Very Feasible), the material expert validation obtained 80% (Feasible), and the average practitioner validation reached 80.48% (Feasible). Black box testing confirmed that all features functioned according to the design without errors, and the limited trial produced a user-acceptance percentage of 87.78% (Very Feasible). These findings indicate that the Digital Village application (SMAPAN) is feasible for improving the effectiveness, efficiency, and transparency of administrative services in Pandan Village.